The importance of corporate image in the marketing of university postgraduate programs / Zainudin Awang. - Awang, Zainudin (Universiti Teknologi MARA Cawangan Selangor, 2010)
The increase in the number of universities offering higher education has surpassed the increase in demand for higher education. Hence, the competition for potential customers, especially postgraduates, is very stiff. When the characteristics of service offering have become uniform, universities should be looking for their own competitive edge in the market to differentiate themselves from their competitors. This study attempts to investigate the influence of the corporate image of a university on the willingness of their outgoing undergraduates to continue postgraduate studies at the university (market retention) and to recommend their friends, families, and employers to engage with the university (positive word of mouth). Data was collected randomly from 872 outgoing undergraduates using self-administered questionnaires. Factor analysis or corporate image items extracted three distinct dimensions. The study renamed these dimensions as the image of a university, image of its academic programs and the external recognition received by the university. As for the students’ loyalty, the factor analysis extracted two distinct dimensions. The study renamed these dimensions as market retention and positive recommendation. The study found that the corporate image of a university had a significant and direct effect on students’ intention to enroll in postgraduate programs at the university. Among the influential corporate image dimensions are the image of a university and the image of its academic programs. The corporate image of a university provides a significant influence on positive word of mouth and recommendations by outgoing undergraduates to potential postgraduate customers to register with the university. The results have significant implications for the long-term growth and survival of postgraduate programs.